From clinical to benchside: lacticaseibacillus and faecalibacterium are positively associated with muscle health and alleviate age-related muscle disorder - Liu, Chaoran; Wong, Pui Yan; Barua, Nilakshi; Li, Baoqi; Wong, Hei Yuet; Zhang, Ning; Chow, Simon Kwoon Ho; Wong, Sunny Hei; Yu, Jun; Ip, Margaret; Cheung, Wing Hoi; Duque, Gustavo; et al. (Aging cell, 2025)
Sarcopenia is an age-related muscle disorder that increases risks of adverse clinical outcomes, but its treatments are still limited. Gut microbiota is potentially associated with sarcopenia, and its role is still unclear. To investigate the role of gut microbiota in sarcopenia, we first compared gut microbiota and metabolites composition in old participants with or without sarcopenia. Fecal microbiota transplantation (FMT) from human donors to antibiotic-treated recipient mice was then performed. Specific probiotics and their mechanisms to treat aged mice were identified. Old people with sarcopenia had different microbial composition and metabolites, including Paraprevotella, Lachnospira, short-chain fatty acids, and purine. After FMT, mice receiving microbes from people with sarcopenia displayed lower muscle mass and strength compared with those receiving microbes from non-sarcopenic donors. Lacticaseibacillus rhamnosus (LR) and Faecalibacterium prausnitzii (FP) were positively related to muscle health of old people, and enhanced muscle mass and function of aged mice. Transcriptomics showed that genes related to tricarboxylic acid cycle (TCA) were enriched after treatments. Metabolic analysis showed increased substrates of TCA cycle in both LR and FP supernatants. Muscle mitochondria density, ATP content, NAD+/NADH, mitochondrial dynamics and biogenesis proteins, as well as colon tight junction proteins of aged mice were improved by both probiotics. LR and the combination of two probiotics also benefit intestinal immune health by reducing CD8+ IFNγ+ T cells. Gut microbiota dysbiosis is a pathogenesis of sarcopenia, and muscle-related probiotics could alleviate age-related muscle disorders mainly through mitochondria improvement. Further clinical translation is warranted.